Building holistic brands: an exploratory study of Halal cosmetics. (9th March 2015) - Aoun, Isabelle; Tournois, Laurent
Abstract : Purpose: – Branding in faith-based consumer markets, in which marketing practices, religion, and consumption intersect, is largely unexplored. The purpose of this paper is to investigate how brands integrate religious concerns into their strategies through Halal branding. The central logic of authors' view is that branding applied in a particular consumer market (i.e., Muslim) could enrich dominant (Western) branding theory. Design/methodology/approach: – Although challenging, qualitative research offers a valuable lens in international marketing research in allowing researchers to study organizations and contexts in their natural settings, enabling a more holistic approach, instead of imposing one's culturally informed pre-conceptions (Boyacigiller and Adler, 1991). In this regard, a multiple case study approach considering Halal cosmetic brands is used. A replication logic is applied in interpreting the data. Findings: – Holistic branding is a broader concept than what mainstream theory acknowledges; brand attributes go beyond the functional and emotional, offering insights into a spiritual dimension. The proposed model identifies attributes that reflect the brand's worldview and contribute to holistic branding: spiritual ethos and belief system, sustainable and eco-ethical philosophy, wholesomeness and inclusiveness. Research limitations/implications: – This exploratory research represents the initial step for faith-based/Halal branding; the discussion is confined to the cases under study. The results are not conclusive and require further empirical research to validate their broader applicability. Practical implications: – The study highlights the need for a comprehensive approach to branding of faith-based products. The Halal market (cosmetics and toiletries) may be attractive to companies that seek to widely develop products targeting faith-based Muslim consumer markets. Originality/value: – The study contributes to an area of growing concern from an academic point of view (i.e. Halal branding) by proposing to add a spiritual dimension to holistic branding. Several questions remain and should stimulate further research. Hence, researchers would be able to understand more clearly the meaning of the religious environment and the impact that environmental forces are likely to exert on business decisions.